Social work and the penal state. Issue 1 (2nd January 2017) - Cummins, Ian
ABSTRACT: The Criminal Justice System (CJS) has historically been a key site of social work intervention. Wacquant argues that the growth of social insecurity and the expansion of the penal state are endogenous features of the neo-liberal political project. The key premises of neo-liberalism have been accepted by parties of both the left and the right. This shift alongside an increase in inequality had led to increasing social anxiety and mistrust. One manifestation of these trends is a decline in the belief that the rehabilitation of offenders is a realisable goal of social and penal policy. The expansion of the penal state: the increasing numbers, poor conditions and the over-representation of minority groups mean that it should be a core social work concern. The paper outlines the ways, in which, risk and managerialism have side lined core social work values in the CJS. It concludes penal policy and conditions can only be reformed if the inherent dignity of offenders is rediscovered and placed at its centre.